An unexpected cause of severe metabolic acidosis - Suzanne K. Veneman; Stephanie E. Veneman; Hardjit Kharagjitsing; Thiemo F. Veneman (European Journal of Case Reports in Internal Medicine)
Introduction: Metabolic acidosis is a potentially serious electrolyte disorder with a variety of potential causes. It can cause serious harm to multiple organ systems with irreversible damage and if untreated it can even cause mortality. Case description: A 66-year-old man presented at the emergency room of our hospital because of abdominal pain, nausea, and vomiting for 3 days, with no diarrhoea. Physical examination showed a sick, restless, shaking, middle-aged man with a maximal eye-motor-verbal score. He had a history of polycythaemia vera but had been lost to follow-up. He was clinically dehydrated with extremely dry mucous membranes and complaining of thirst. Laboratory investigations showed severe metabolic acidosis with a pH of 7.08 and electrolyte disturbances with hyperkalaemia and hyponatremia. The treatment with a high dose of hydroxyurea had been re-started 14 days before presentation at the emergency room. Conclusion: We believe that the recent initiation of the treatment with a (too) high dose of hydroxyurea with consequently gastrointestinal complications could have been the underlying cause. In addition to the indirect effect of dehydration resulting from the gastrointestinal side effects of hydroxyurea, another known but rarely reported adverse effect is (tubular) renal dysfunction, which may have contributed to the progression of metabolic acidosis. The exact mechanisms by which hydroxyurea induces metabolic acidosis remain unknown. It is important to recognize hydroxyurea as the culprit of the development of severe metabolic acidosis. If unrecognized, metabolic acidosis can worsen and cause irreversible damage.